Chemically strengthened glass with film and method for measuring surface stress of chemically strengthened glass

JP7652023B2Active Publication Date: 2025-03-27AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021146401
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-09
Filing Date
2021-09-08
Publication Date
2025-03-27
Estimated Expiration
2041-09-08

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、表面におけるカリウムイオンによる圧縮応力の深さが非常に浅いにも関わらず、表面伝搬光を利用してガラス表面の圧縮応力を測定できる化学強化ガラスを提供できる。また、上記化学強化ガラスを対象とした新たな表面応力測定方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652023000002
    Figure 0007652023000002
  • Figure 0007652023000003
    Figure 0007652023000003
  • Figure 0007652023000004
    Figure 0007652023000004
Patent Text Reader

Abstract

To provide a chemically strengthened glass with a film, capable of making new measurement of surface stress applicable to a chemically strengthened glass having obscure interference fringes using surface propagation light, and making measurement of compressive stress on a surface greatly difficult or impossible.SOLUTION: A chemically strengthened glass with a film comprises a chemically strengthened glass having a pair of principal surfaces facing each other, and a film formed on at least one of the principal surfaces of the chemically strengthened glass. The chemically strengthened glass with a film has two or less interference fringes observed in stress measurement using surface propagation light with a wavelength of 365 nm, and a refraction index of the film is lower than a refraction index of the chemically strengthened glass.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chemically strengthened glass with a film and a method for measuring the surface stress of chemically strengthened glass. [Background technology]

[0002] Chemically strengthened glass is used for cover glasses of electronic devices such as mobile terminals. Chemically strengthened glass is produced by contacting glass with a molten salt containing alkali metal ions, for example, to cause ion exchange between the alkali metal ions in the glass and the alkali metal ions in the molten salt, thereby forming a compressive stress layer on the surface of the glass. The strength of the resulting chemically strengthened glass strongly depends on the stress profile.

[0003] The cover glass of a mobile terminal or the like may crack due to deformation when the terminal is dropped, etc. In order to prevent such fracture, i.e. fracture due to bending mode, it is effective to increase the compressive stress on the glass surface.

[0004] In addition, the cover glass of a mobile device, etc., may be broken by impact with a protruding object when the device is dropped onto asphalt or sand. In order to prevent such damage, i.e. damage due to impact mode, it is effective to increase the depth of the compressive stress layer and form the compressive stress layer in a deeper part of the glass.

[0005] Specifically, by generating a large compressive stress on the surface of the glass through sodium ion-potassium ion exchange, it is possible to suppress fracture in bending mode, while at the same time, by generating a slightly smaller compressive stress in the deeper part of the glass through lithium ion-sodium ion exchange, it is possible to suppress fracture in impact mode.

[0006] However, when a compressive stress layer is formed on the surface of the glass, a tensile stress corresponding to the compressive stress on the surface is inevitably generated in the center of the glass. If this tensile stress becomes too large, the glass tends to break violently and scatter into pieces when it is broken.

[0007] It is desirable to prevent glass from breaking violently and scattering into fragments when it breaks, while suppressing both bending mode and impact mode fractures.To achieve this, it is conceivable to increase the compressive stress on the glass surface and form a compressive stress layer in a deeper portion, while decreasing the depth of the compressive stress due to sodium ion-potassium ion exchange in the surface portion of the glass. As chemically strengthened glass that has high strength and is less likely to scatter fragments, chemically strengthened glass that has been subjected to a two-stage ion exchange treatment has been disclosed (Patent Document 1). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] U.S. Patent No. 9,487,434 [Patent Document 2] Special Publication No. 59-37451 [Patent Document 3] Patent No. 6713651 Summary of the Invention [Problem to be solved by the invention]

[0009] In general, the stress in the area where sodium ions in the surface layer of glass have been exchanged for potassium ions can be obtained from interference fringes using light propagating within the surface layer of the glass, i.e., surface-propagated light (Reference 2). However, it was discovered that if the depth of the compressive stress caused by potassium ions in the surface part of the glass is made extremely shallower than before, the interference fringes become unclear.

[0010] The number of observed interference fringes can be increased by shortening the wavelength of the light propagating through the surface. Nevertheless, even when light with a wavelength of 365 nm is used, there are cases where the number of observed interference fringes is two or less. When the number of interference fringes is two or less, in particular, the fringes become unclear and it becomes very difficult to determine the compressive stress on the glass surface.

[0011] Therefore, the present invention aims to provide a new surface stress measurement method for chemically strengthened glass, in which interference fringes using surface-propagated light are unclear and it is very difficult or impossible to measure the compressive stress on the surface, and to provide chemically strengthened glass with a film that enables such measurement. [Means for solving the problem]

[0012] As a result of intensive research, the present inventors have found that the above problem can be solved by forming a film having a lower refractive index than that of chemically strengthened glass on the main surface of the chemically strengthened glass. This is contrary to the conventional knowledge that the glass surface is immersed in a liquid having a refractive index equal to or higher than that of glass in order to measure surface-propagated light, and will be specifically described below.

[0013] When chemically strengthened glass is used for the display of electronic devices such as mobile phones and smartphones, a film may be formed on the main surface of the chemically strengthened glass for the purpose of imparting anti-glare, antibacterial, anti-fouling effects, etc. The refractive index of these films is lower than that of the chemically strengthened glass. However, when anti-glare, antibacterial, or anti-fouling films are formed for these purposes, it was thought that interference fringes caused by light propagating through the surface would be difficult to observe compared to chemically strengthened glass that does not have a film (Reference 3). In contrast, in the present invention, when the depth of the compressive stress due to potassium ions on the surface of chemically strengthened glass is very shallow and the interference fringes using surface-propagated light become unclear, the interference fringes are formed by forming a film with a low refractive index. It has been found that this makes the interference fringes clearer.

[0014] That is, the present invention is as follows. [1] A chemically strengthened glass having a pair of main surfaces facing each other, and a film formed on at least one of the main surfaces of the chemically strengthened glass, The chemically strengthened glass has two or less interference fringes observed in stress measurement using surface-propagated light having a wavelength of 365 nm, A chemically strengthened glass with a film, wherein the refractive index of the film is lower than the refractive index of the chemically strengthened glass. [2] The chemically strengthened glass with a film according to the above [1], wherein the difference between the refractive index of the film and the refractive index of the chemically strengthened glass is 0.02 to 0.30. [3] The chemically strengthened glass with a film according to [1] or [2], wherein a stress depth of a deep layer of the chemically strengthened glass is 0.1 × t or more, where t is a thickness of the chemically strengthened glass. [4] The chemically strengthened glass with a film according to any one of [1] to [3] above, wherein a matrix composition of the chemically strengthened glass contains 5 mol% or more of Li2O, expressed in mole percentage based on oxides. [5] The chemically strengthened glass with a film according to any one of the above [1] to [4], wherein the film has a thickness of 2 to 50 nm. [6] The chemically strengthened glass with a film according to any one of [1] to [5] above, wherein the film contains a fluorine-based organic compound.

[0015] [7] A method for measuring surface stress of chemically strengthened glass having a pair of main surfaces facing each other, comprising: The chemically strengthened glass has two or less interference fringes observed in stress measurement using surface-propagated light having a wavelength of 365 nm, Forming a film having a lower refractive index than the chemically strengthened glass on at least one main surface of the chemically strengthened glass to obtain a film-coated chemically strengthened glass; and The surface stress of the chemically strengthened glass is measured by measuring the surface compressive stress of the chemically strengthened glass using a surface-propagated light. [8] The surface stress of the chemically strengthened glass according to [7], wherein the surface-propagated light has a wavelength of 650 nm or less. Effect of the Invention

[0016] According to the present invention, a chemically strengthened glass can be provided in which the compressive stress of the glass surface can be measured using surface-propagating light, even though the depth of the compressive stress due to potassium ions on the surface is very shallow. In addition, a new surface stress measurement method for the chemically strengthened glass can be provided. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is an image of interference fringes obtained by measuring the chemically strengthened glass of Example 1 with a surface stress meter. [Diagram 2] FIG. 2 is an image of interference fringes obtained by measuring the chemically strengthened glass of Example 2 with a surface stress meter. [Diagram 3] FIG. 3 is an image of interference fringes obtained by measuring the chemically strengthened glass with the film of Example 3 using a surface stress meter. [Figure 4] FIG. 4 is an image of interference fringes obtained by measuring the chemically strengthened glass with the film of Example 4 using a surface stress meter. [Diagram 5] FIG. 5 is an image of interference fringes obtained by measuring the chemically strengthened glass with the film of Example 5 using a surface stress meter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] <Chemically strengthened glass with film> The film-attached chemically strengthened glass according to this embodiment comprises chemically strengthened glass having a pair of mutually opposing main surfaces, and a film formed on at least one of the main surfaces. Chemically strengthened glass has two or fewer interference fringes observed in stress measurements using surface-propagated light with a wavelength of 365 nm. The refractive index of the film formed on at least one principal surface of the chemically strengthened glass is lower than the refractive index of the chemically strengthened glass.

[0019] Chemically strengthened glass has two or fewer interference fringes observed in stress measurements using surface-propagated light with a wavelength of 365 nm. In this specification, two or less interference fringes means that no interference fringes are observed, or the number of observed interference fringes is one or two.

[0020] The surface compressive stress and its depth are calculated from the intervals between the observed interference fringes. If the number of interference fringes is three or more, the data information increases and is connected, and the accuracy of the calculated surface compressive stress and its depth increases. On the other hand, if the number of interference fringes is two or less, the fringes tend to become unclear, making it difficult to calculate the surface compressive stress and its depth. The wavelength of the surface propagating light used for stress measurement is, for example, 790 nm, 596 nm, 365 nm, etc., and the shorter the wavelength, the clearer the observed interference fringes are and the more numerous they are. In this specification, the term "obscured interference fringes" means that when stress measurement is performed using surface propagating light with a wavelength of 365 nm, the interference fringes are not clear enough to detect the position of the observed fringes or the inclination angle of the fringes and automatically measure the surface compressive stress.

[0021] However, when the depth of the compressive stress due to potassium ions in the surface portion of the chemically strengthened glass is extremely shallow, even if surface-propagated light with a wavelength of 365 nm is used, the interference fringes become unclear and the number of fringes is 2 or less. In this case, the surface compressive stress and its depth cannot be obtained appropriately.

[0022] The reason why the interference fringes become unclear when the depth of the compressive stress due to potassium ions is extremely shallow is presumed to be as follows. Stress measurement using surface propagating light is a method of measuring stress using the interference fringes of light propagating through the high refractive index area of ​​the glass surface, which is caused by replacing sodium ions on the glass surface with potassium ions. Therefore, if the area in which light can propagate is narrow, the propagating light spreads and the interference fringes become unclear. This can be explained by referring to the light propagation phenomenon in optical fibers, where light propagates through a core that also has a high refractive index.

[0023] There are two factors that cause the beam diameter to increase in optical fibers: (i) The core diameter, which is the light propagation region, is small, i.e., the region with a high refractive index is small. (ii) The difference in refractive index between the core and the cladding is small. When considering the above factors in terms of their application to stress measurement using surface-propagated light, the following two points are considered to be factors that cause interference fringes to spread and become unclear. (i)' The stress layer which becomes the light propagation region is shallow; (ii)' The surface compressive stress is small. In this way, if the compressive stress due to ion-exchanged potassium ions, i.e., the surface compressive stress of the glass, is small or the stress depth is shallow, the area through which light propagates becomes narrow and the propagating light spreads, causing the interference fringes to become unclear.

[0024] If a film with a refractive index lower than that of the chemically strengthened glass (hereinafter sometimes referred to as a "low refractive index film") is formed on at least one of the main surfaces of such chemically strengthened glass, when stress measurement is performed using surface-propagated light with a wavelength of 365 nm, even if there are two interference fringes, the interference fringes become clear, and surface compressive stress can be automatically measured.

[0025] This is the opposite of the conventional knowledge that, when a film with a lower refractive index than chemically strengthened glass, such as an anti-glare film, antibacterial film, or anti-soiling film, is formed on the main surface, interference fringes caused by surface-propagating light cannot be observed as well as with chemically strengthened glass that does not have a film formed on it. The reason for this is believed to be that when the depth of the surface compressive stress of the chemically strengthened glass is very shallow, the region in which the refractive index of the surface of the chemically strengthened glass changes due to the chemical strengthening treatment is small. That is, when the depth of the surface stress is very shallow, the refractive index change region is small and the propagating light spreads, whereas it is presumed that the spread of the propagating light can be suppressed by forming a low refractive index film.

[0026] The effect of making interference fringes clearly observable due to the presence of a low refractive index film can be obtained regardless of the type or number of low refractive index films or the presence of other layers. That is, one type of low refractive index film may be formed, or two or more types may be formed, or one type of low refractive index film may be formed in multiple layers. Also, the low refractive index film may be formed directly on the main surface of the chemically strengthened glass, or another layer may be formed between the chemically strengthened glass and the low refractive index film. Such another layer may be a film having a higher refractive index than the chemically strengthened glass (hereinafter, sometimes referred to as a "high refractive index film"). The low refractive index film may be formed on at least one of the main surfaces of the chemically strengthened glass, and may be formed on both main surfaces.

[0027] The effect of making the interference fringes of the film-attached chemically strengthened glass clear is due to the refractive index distribution. Therefore, the film-attached chemically strengthened glass is preferably formed in the order of, for example, chemically strengthened glass-low refractive index film, glass-low refractive index film-high refractive index film, glass-high refractive index film-low refractive index film, glass-high refractive index film-low refractive index film-high refractive index film, etc.

[0028] Refractive index n of chemically strengthened glass g and the refractive index of the low refractive index film, n m Difference from (n g -n m ) is preferably 0.02 or more, more preferably 0.03 or more, even more preferably 0.05 or more, and even more preferably 0.07 or more, from the viewpoint of suppressing the spread of propagating light. On the other hand, from the viewpoint of preventing total reflection occurring between the chemically strengthened glass and the low refractive index film, which makes it difficult to measure stress with a surface stress meter, the difference in refractive index is preferably 0.30 or less, more preferably 0.25 or less, even more preferably 0.20 or less, and even more preferably 0.15 or less. Refractive index n of chemically strengthened glass g and the refractive index n of the low refractive index film m is measured by a refractometer.

[0029] (Chemically strengthened glass) The glass before chemical strengthening treatment is not particularly limited as long as it is chemically strengthened, but it is preferable that the glass contains an alkali metal having a small ionic radius, such as lithium, sodium, etc. Examples of such glass include aluminosilicate glass, soda lime silicate glass, borosilicate glass, lead glass, alkali barium glass, and aluminoborosilicate glass. In this specification, the glass after chemical strengthening is referred to as "chemically strengthened glass", but the matrix composition of the chemically strengthened glass is the same as that of the glass before chemical strengthening. The matrix composition of the chemically strengthened glass is the composition inside the glass excluding the layer in which ion exchange has been performed by the chemical strengthening treatment.

[0030] The depth of surface stress at which two or fewer interference fringes are observed cannot be clearly defined because it varies depending on the matrix composition of the chemically strengthened glass, the surface compressive stress, and the depth of the diffused potassium ions. However, the depth of the surface stress at which two or less interference fringes are observed is generally 4 μm or less when, for example, glass containing general alkali ions is chemically strengthened. The lower limit of the depth of the surface stress is not particularly limited, but is, for example, 1.8 μm or more.

[0031] The surface compressive stress at which two or less interference fringes are observed is generally 1200 MPa or less when, for example, a glass containing general alkali ions is chemically strengthened. There is no particular lower limit to the surface compressive stress, but in consideration of the use as a cover glass, it is preferably 400 MPa or more, more preferably 550 MPa or more, and even more preferably 700 MPa or more.

[0032] The surface compressive stress and the depth of the surface stress are measured by a surface stress meter using surface-propagating light, i.e., an optical waveguide surface stress meter. The stress depth of a deep layer of the chemically strengthened glass described below is measured by a scattered light photoelastic stress meter. Although the optical waveguide surface stress meter can measure stress accurately in a short time, it can only measure stress when the refractive index decreases from the surface to the inside of the sample. Therefore, it is suitable for measuring the surface compressive stress of chemically strengthened glass in which sodium ions are exchanged for potassium ions. A specific example is the FSM-6000 manufactured by Orihara Seisakusho. Although the scattered light photoelastic stress meter can measure stress regardless of the refractive index distribution, it is susceptible to surface scattering and may not be able to accurately measure stress near the surface. Therefore, it is suitable for measuring stress deep inside chemically strengthened glass in which lithium ions have been ion-exchanged with sodium ions. A specific example is the SLP2000 manufactured by Orihara Seisakusho. That is, by using a combination of an optical waveguide surface stress meter and a scattered light photoelastic stress meter, an accurate stress profile can be obtained.

[0033] Refractive index n of chemically strengthened glass g is not particularly limited as long as it is higher than the low refractive index film. The refractive index is preferably 1.30 or more, more preferably 1.35 or more, and even more preferably 1.40 or more, from the viewpoint of preventing total reflection occurring between the chemically strengthened glass and the low refractive index film, making it difficult to measure stress with a surface stress meter. In addition, from the viewpoint of suppressing the spread of propagating light, the refractive index is preferably 1.54 or less, more preferably 1.52 or less, even more preferably 1.50 or less, and even more preferably 1.48 or less.

[0034] Since chemically strengthened glass generates a large compressive stress due to ion exchange between sodium ions and potassium ions in the surface portion, the matrix composition preferably contains Na2O. The content of Na2O is more preferably 2 mol% or more, more preferably 3 mol% or more, even more preferably 4 mol% or more, and particularly preferably 5 mol% or more. In addition, the upper limit of the content of Na2O is not particularly limited, but from the viewpoint of increasing the stress in the deep layer of the glass, it is preferably 12 mol% or less, more preferably 10 mol% or less, and even more preferably 8 mol% or less. In addition, the matrix composition of chemically strengthened glass in this specification is expressed in mole percentage based on oxides unless otherwise specified.

[0035] It is preferable that the surface compressive stress and the depth of the surface stress be within the above-mentioned preferred ranges by ion exchange with potassium ions.

[0036] In the deeper part of the chemically strengthened glass, a relatively small compressive stress occurs due to ion exchange between lithium ions and sodium ions, so the matrix composition preferably contains Li2O. The content of Li2O is more preferably 5 mol% or more, even more preferably 6 mol% or more, and even more preferably 8 mol% or more. In addition, the upper limit of the content of Li2O is not particularly limited, but from the viewpoint of devitrification during glass molding, it is preferably 14 mol% or less, more preferably 12 mol% or less, and even more preferably 11 mol% or less.

[0037] A region deeper than the surface portion where compressive stress is generated by potassium ions and where a compressive stress layer is formed by sodium ions is referred to as a deep layer of chemically strengthened glass. From the viewpoint of strength when dropped, the stress depth of the deep layer of the chemically strengthened glass is preferably (0.01 × t) or more, more preferably (0.012 × t) or more, even more preferably (0.1 × t) or more, even more preferably (0.12 × t) or more, and particularly preferably (0.15 × t) or more, with respect to the thickness t of the chemically strengthened glass. The upper limit of the stress depth of the deep layer is preferably (0.25 × t) or less, more preferably (0.23 × t) or less, and even more preferably (0.21 × t) or less, from the viewpoint of preventing the glass from shattering when broken. The stress depth in the deep layer of the chemically strengthened glass can be measured by a scattered light photoelastic stress meter.

[0038] The thickness t of the chemically strengthened glass is not particularly limited, but for example, when used as a cover glass for a mobile device, it is preferably 0.1 mm or more, more preferably 0.2 mm or more, even more preferably 0.5 mm or more, and preferably 2.5 mm or less, more preferably 1.5 mm or less, and even more preferably 1 mm or less. When used in an image display device such as a display device, car navigation, console panel, or instrument panel, the thickness t of the chemically strengthened glass is preferably 0.1 mm or more, more preferably 0.2 mm or more, even more preferably 0.5 mm or more, and preferably 2.1 mm or less, more preferably 1.8 mm or less, and even more preferably 1.5 mm or less.

[0039] If the specific matrix composition of the chemically strengthened glass is, for example, as follows, a preferable stress profile is easily formed by the chemical strengthening treatment. It is preferable that the material contains, in terms of mole percentage based on oxides, 50-80% SiO2, 8-20% Al2O3, 0-10% B2O3, 5-14% Li2O, 2-12% Na2O, and 0-10% K2O, and that the total content of MgO, CaO, SrO, and BaO (MgO+CaO+SrO+BaO) is 0-10%, and the total content of ZrO2 and TiO2 (ZrO2+TiO2) is 0-5%.

[0040] Each component of the glass composition will be described in detail below. SiO2 is a component that constitutes the skeleton of glass. It also increases chemical durability and reduces the occurrence of cracks when the glass surface is scratched. The SiO2 content is preferably 50% or more, more preferably 55% or more, and even more preferably 58% or more. In order to increase the meltability of the glass, the SiO2 content is preferably 80% or less, more preferably 75% or less, and even more preferably 70% or less.

[0041] Al2O3 is an effective component for improving ion exchangeability during chemical strengthening and increasing the surface compressive stress after strengthening, and is also a component for increasing the glass transition temperature (Tg) and Young's modulus. The content of Al2O3 is preferably 8% or more, more preferably 10% or more, and even more preferably 12% or more. In order to improve the melting property, the content of Al2O3 is preferably 20% or less, more preferably 18% or less, and further preferably 15% or less.

[0042] B2O3 is not essential, but may be added to improve meltability during glass production, etc. When B2O3 is contained, the content is preferably 0.5% or more, more preferably 1% or more, and even more preferably 2% or more. In order to prevent the occurrence of striae during melting, which would deteriorate the quality of the glass to be subjected to chemical strengthening treatment, the content of B2O3 is preferably 10% or less, more preferably 8% or less, even more preferably 5% or less, even more preferably 3% or less, and particularly preferably 1% or less. In order to increase the acid resistance, it is preferable that B2O3 is not substantially contained. In this specification, "substantially free" means that it is not contained except for unavoidable impurities contained in raw materials, that is, it is not intentionally contained. Specifically, it means that the content in the matrix composition of the glass is less than 0.1 mol%.

[0043] Li2O is a component necessary for forming a compressive stress deep inside the glass by ion exchange, and is preferably contained within the above-mentioned range.

[0044] Na2O is a component that forms a surface compressive stress layer by ion exchange with potassium ions during chemical strengthening treatment, and is preferably contained within the above-mentioned range.

[0045] K2O is not essential, but may be contained to improve the meltability of the glass and suppress devitrification. The content of K2O is preferably 0.5% or more, more preferably 1% or more, and even more preferably 1.2% or more. In order to increase the compressive stress due to ion exchange, the content of K2O is preferably 10% or less, more preferably 9% or less, and even more preferably 8% or less.

[0046] Alkali metal oxides such as Li2O, Na2O, and K2O are all components that lower the melting temperature of glass. The total content of Li2O, Na2O, and K2O (Li2O+Na2O+K2O) is preferably 7% or more, more preferably 9% or more, even more preferably 11% or more, and even more preferably 13% or more. In order to maintain the strength of the glass, the content of (Li2O+Na2O+K2O) is preferably 24% or less, and more preferably 20% or less.

[0047] Alkaline earth metal oxides such as MgO, CaO, SrO, and BaO are components that enhance the meltability of glass, but on the other hand, they tend to reduce the ion exchange performance. Therefore, the total content of MgO, CaO, SrO and BaO (MgO+CaO+SrO+BaO) is preferably 10% or less, and more preferably 5% or less.

[0048] In the case where any one of MgO, CaO, SrO and BaO is contained, it is preferable to contain MgO in order to increase the strength of the chemically strengthened glass. When MgO is contained, the content of MgO is preferably 0.1% or more, more preferably 0.3% or more, and further preferably 0.5% or more. In order to improve the ion exchange performance, the MgO content is preferably 10% or less, and more preferably 5% or less.

[0049] In the case where CaO is contained, the CaO content is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, and particularly preferably 1% or more. From the viewpoint of improving the ion exchange performance, the CaO content is preferably 5% or less, more preferably 1% or less, and even more preferably substantially none is contained.

[0050] When SrO is contained, the content of SrO is preferably 0.5% or more, and more preferably 1% or more. In order to improve the ion exchange performance, the SrO content is preferably 5% or less, more preferably 1% or less, and even more preferably substantially none.

[0051] In the case where BaO is contained, the content of BaO is preferably 0.5% or more, and more preferably 1% or more. In order to improve the ion exchange performance, the BaO content is preferably 5% or less, more preferably 1% or less, and even more preferably substantially none is contained.

[0052] ZnO is a component that improves the meltability of glass and may be contained. When ZnO is contained, the content of ZnO is preferably 0.2% or more, and more preferably 0.5% or more. In order to improve the weather resistance of the glass, the ZnO content is preferably 5% or less, more preferably 1% or less, and even more preferably substantially none is contained.

[0053] TiO2 is a component that improves the crushability of chemically strengthened glass and may be contained. When TiO2 is contained, the content of TiO2 is preferably 0.1% or more. In order to suppress devitrification during melting, the TiO2 content is preferably 5% or less, more preferably 1% or less, and even more preferably substantially none is contained.

[0054] ZrO2 is a component that increases the surface compressive stress due to ion exchange, and may be contained. When ZrO2 is contained, the content of ZrO2 is preferably 0.3% or more, more preferably 0.5% or more, further preferably 0.7% or more, and more preferably 1% or more. In order to suppress devitrification during melting, the content of ZrO2 is preferably 5% or less, and more preferably 3% or less.

[0055] The total content of TiO2 and ZrO2 (TiO2 + ZrO2) is preferably 5% or less, and more preferably 3% or less.

[0056] Y2O3, La2O3, and Nb2O5 are components that improve the crushability of chemically strengthened glass and may be contained. From the above viewpoint, the content of each of these components when contained is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, even more preferably 2% or more, and particularly preferably 2.5% or more.

[0057] The total content of Y2O3, La2O3 and Nb2O5 (Y2O3 + La2O3 + Nb2O5) is preferably 9% or less, and more preferably 8% or less, in order to prevent the glass from devitrifying during melting and to prevent a deterioration in the quality of the chemically strengthened glass. From the above viewpoints, the content of each of Y2O3, La2O3, and Nb2O5 is preferably 3% or less, more preferably 2% or less, further preferably 1% or less, more preferably 0.7% or less, and particularly preferably 0.3% or less.

[0058] Ta2O5 and Gd2O3 may be contained in small amounts to improve the crushability of the chemically strengthened glass. In order to prevent the refractive index and reflectance from becoming too high, the content of each of Ta2O5 and Gd2O3 is preferably 1% or less, more preferably 0.5% or less, and even more preferably substantially none.

[0059] P2O5 may be contained to improve ion exchange performance. When P2O5 is contained, the content of P2O5 is preferably 0.5% or more, and more preferably 1% or more. In order to improve chemical durability, the content of P2O5 is preferably 2% or less, and more preferably substantially zero.

[0060] When coloring glass, a coloring component may be added to the glass as long as it does not impede the achievement of the desired chemical strengthening properties. Suitable examples of the coloring component include Co3O4, MnO2, Fe2O3, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, TiO2, CeO2, Er2O3, and Nd2O3. These may be used alone or in combination.

[0061] In order to suppress devitrification of the glass, the total content of the coloring components is preferably 7% or less, more preferably 5% or less, even more preferably 3% or less, and even more preferably 1% or less. In addition, when it is desired to increase the visible light transmittance of the glass, it is preferable that these coloring components are not substantially contained.

[0062] As a fining agent for melting glass, SO3, chlorides, fluorides, etc. may be appropriately contained. It is preferable that As2O3 is not substantially contained. When Sb2O3 is contained, the content of Sb2O3 is preferably 0.3% or less, more preferably 0.1% or less, and most preferably substantially not contained.

[0063] (Low refractive index film) The low refractive index film in this embodiment has a refractive index lower than that of chemically strengthened glass. Refractive index n of low refractive index film m is not particularly limited as long as it is lower than that of chemically strengthened glass, but from the viewpoint of making interference fringes clear, it is preferably 1.52 or less, more preferably 1.50 or less, even more preferably 1.48 or less, and most preferably 1.45 or less. In addition, from the viewpoint of preventing total reflection between the chemically strengthened glass and the low refractive index film, which makes it difficult to measure with a surface stress meter, the refractive index is preferably 1.25 or more, more preferably 1.30 or more, and even more preferably 1.35 or more.

[0064] The thickness of the low refractive index film is preferably 2 nm or more from the viewpoint of suppressing the spread of propagating light, more preferably 5 nm or more, even more preferably 8 nm or more, even more preferably 10 nm or more, and particularly preferably 15 nm or more. In addition, from the viewpoint of preventing total reflection occurring between the chemically strengthened glass and the low refractive index film, which makes it difficult to measure stress using a surface stress meter, the thickness of the low refractive index film is preferably 200 nm or less, more preferably 100 nm or less, even more preferably 50 nm or less, and even more preferably 30 nm or less. When the low refractive index film is made up of two or more layers, it is preferable that the total film thickness falls within the above range.

[0065] The low refractive index film may have one or more properties selected from the group consisting of antifouling, water repellency, oil repellency, hydrophilicity, and lipophilicity. A low refractive index film having the above properties is called an antifouling layer. The antifouling layer preferably contains a fluorine-based organic compound.

[0066] Examples of the fluorine-based organic compound include perfluoroalkyl group-containing compounds and perfluoropolyether group-containing compounds, and a silane compound having a perfluoropolyether group is preferred.

[0067] Examples of the silane compound having a perfluoropolyether group include a material containing a compound represented by the following formula A and / or a partial hydrolysis condensate thereof. Rf 3 -Rf 2 -Z 1 Formula A In formula A, Rf 3 is the group: C m F 2m+1 (wherein m is an integer from 1 to 6); Rf 2 is the group: -O-(C a F 2a O) n - (wherein a is an integer from 1 to 6, n is an integer of 1 or more, and when n is 2 or more, each -C a F 2a The O-units may be the same or different; Z 1 is the group: -Q 2 -{CH2CH(SiR 2 q X 2 3-q )} r -H (where Q 2 is -(CH2) s - (wherein s is an integer of 0 to 12), or -(CH2) containing one or more bonds selected from an ester bond, an ether bond, an amide bond, a urethane bond, and a phenylene group. s-, some or all of the -CH2- units may be replaced by -CF2- units and / or -CF(CF3)- units, R 2 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms, which may contain a substituent; X 2 are each independently a hydroxyl group or a hydrolyzable group, q is an integer of 0 to 2, and r is an integer of 1 to 20. X 2 Examples of the hydrolyzable group in include an alkoxy group, an acyloxy group, a ketoxime group, an alkenyloxy group, an amino group, an aminoxy group, an amide group, an isocyanate group, and a halogen atom. Among these, from the viewpoint of the balance between stability and ease of hydrolysis, an alkoxy group, an isocyanate group, and a halogen atom (particularly a chlorine atom) are preferred. As the alkoxy group, an alkoxy group having 1 to 3 carbon atoms is preferred, and a methoxy group or an ethoxy group is more preferred.

[0068] For example, commercially available products such as "Afluid (registered trademark) S-550" (product name, manufactured by AGC Inc.), "KP-801" (product name, manufactured by Shin-Etsu Chemical Co., Ltd.), "X-71" (product name, manufactured by Shin-Etsu Chemical Co., Ltd.), "KY-130" (product name, manufactured by Shin-Etsu Chemical Co., Ltd.), "KY-178" (product name, manufactured by Shin-Etsu Chemical Co., Ltd.), "KY-185" (product name, manufactured by Shin-Etsu Chemical Co., Ltd.), "KY-195" (product name, manufactured by Shin-Etsu Chemical Co., Ltd.), and "Optool (registered trademark) DSX (product name, manufactured by Daikin Industries, Ltd.)" can be used. Furthermore, commercially available products to which oil, antistatic agents, etc. have been added can also be used.

[0069] In order to increase the adhesion of the low refractive index film serving as the antifouling layer to the chemically strengthened glass, silicon dioxide, alumina, or the like may be used as an adhesion layer as the low refractive index film, and it is preferable that the adhesion layer is composed mainly of silicon dioxide. In this case, it is preferable that the adhesion layer is between the antifouling layer and the chemically strengthened glass. However, the low refractive index film serving as the adhesive layer may be used alone without being used in combination with the low refractive index film serving as the antifouling layer.

[0070] Chemically strengthened glass with a film is particularly useful as a cover glass for mobile devices such as mobile phones and smartphones. It is also useful as a cover glass for display devices such as televisions, personal computers, and touch panels that are not intended to be portable. It is also useful for elevator walls, walls of buildings such as houses and buildings, i.e., full-surface displays. In addition to the above, it is also useful as building materials such as window glass, table tops, interiors of automobiles and airplanes, and cover glass for these, and for applications such as curved housings.

[0071] <Method of manufacturing chemically strengthened glass with film> In the present embodiment, the glass before the chemical strengthening treatment can be produced by a conventionally known method. For example, in the case of obtaining a plate-shaped glass, the glass can be produced by the following method. Glass raw materials are mixed to obtain glass of a desired composition, and are heated and melted in a glass melting furnace. The molten glass is then homogenized by bubbling, stirring, adding a clarifier, etc., and formed into a glass plate of a predetermined thickness by a known forming method, and slowly cooled. After homogenization, the molten glass may be formed into a block shape, slowly cooled, and then cut into a plate shape.

[0072] Examples of forming methods for plate glass include the float method, the press method, the fusion method, and the down-draw method. In particular, when producing a large glass plate, the float method is preferred. In addition, continuous forming methods other than the float method, such as the fusion method and the down-draw method, are also preferred.

[0073] The glass composition of the obtained glass can be, for example, the glass matrix composition described in (Chemically strengthened glass) of the above <Chemically strengthened glass with film>, and the preferred embodiments are also the same.

[0074] The obtained glass is then subjected to a chemical strengthening treatment to obtain a chemically strengthened glass. Chemical strengthening is a process in which glass is immersed in a molten solution of a metal salt containing metal ions with a large ionic radius, and metal ions with a small ionic radius in the glass are replaced with metal ions with a large ionic radius. Typically, lithium ions are replaced with sodium ions or potassium ions, and sodium ions are replaced with potassium ions.

[0075] In order to increase the speed of chemical strengthening and to perform ion exchange even in the deep layers of the glass to generate stress, it is preferable to use "Li-Na exchange" in which lithium ions in the glass are exchanged with sodium ions. Also, in order to generate large compressive stress on the surface by ion exchange, it is preferable to use "Na-K exchange" in which sodium ions in the glass are exchanged with potassium ions.

[0076] Examples of molten salts for performing chemical strengthening treatment include nitrates, sulfates, carbonates, and chlorides. Among these, examples of nitrates include lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, and silver nitrate. Examples of sulfates include lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, and silver sulfate. Examples of carbonates include lithium carbonate, sodium carbonate, and potassium carbonate. Examples of chlorides include lithium chloride, sodium chloride, potassium chloride, cesium chloride, and silver chloride. These molten salts may be used alone or in combination of two or more kinds.

[0077] The treatment conditions, such as the time and temperature, of the chemical strengthening treatment are appropriately selected in consideration of the glass composition, the type of molten salt, etc. This results in chemically strengthened glass in which two or fewer interference fringes are observed in stress measurement using surface-propagated light with a wavelength of 365 nm.

[0078] The chemically strengthened glass may be obtained, for example, by the following two-stage chemical strengthening treatment. In the first stage of chemical strengthening treatment, the glass is immersed in a metal salt containing sodium ions, for example, molten sodium nitrate. The temperature of the metal salt is, for example, about 350 to 500°C, and the immersion time is, for example, about 0.1 to 10 hours. This causes ion exchange between the lithium ions in the glass and the sodium ions in the metal salt, forming, for example, a compressive stress layer with a surface compressive stress of 200 MPa or more and a compressive stress layer depth of 80 μm or more. If the surface compressive stress introduced in the first stage treatment exceeds 1000 MPa, it may be difficult to increase the depth of compressive stress layer (DOL) while keeping the internal stress (CT) low in the finally obtained chemically strengthened glass. Therefore, the surface compressive stress introduced in the first stage treatment is preferably 900 MPa or less, more preferably 700 MPa or less, and even more preferably 600 MPa or less.

[0079] In the second stage of chemical strengthening treatment, the glass that has been subjected to the first stage of treatment is immersed in a metal salt containing potassium ions, for example, potassium nitrate molten salt. The temperature of the metal salt is equal to or higher than the melting point of the metal salt, and from the viewpoint of promoting ion exchange, is preferably equal to or higher than 350°C, more preferably equal to or higher than 370°C, and even more preferably equal to or higher than 390°C. Moreover, from the viewpoint of promoting ion exchange, the immersion time in the metal salt is preferably equal to or higher than 10 minutes, more preferably equal to or higher than 20 minutes, and even more preferably equal to or higher than 30 minutes. On the other hand, from the viewpoint of observing two or less interference fringes in stress measurement using surface-propagated light with a wavelength of 365 nm, the temperature of the metal salt is preferably 440° C. or less, more preferably 420° C. or less, and even more preferably 400° C. or less. From the same viewpoint, the immersion time in the metal salt is preferably 90 minutes or less, more preferably 70 minutes or less, and even more preferably 50 minutes or less.

[0080] Although an example of the chemical strengthening treatment is shown above, a three-stage chemical strengthening treatment may be performed. Each chemical strengthening treatment may contain multiple alkali metal ions, such as lithium ions and sodium ions, sodium ions and potassium ions, or lithium ions, sodium ions and potassium ions.

[0081] When performing such a two- or three-stage chemical strengthening treatment, the total treatment time is preferably 10 hours or less, more preferably 5 hours or less, and even more preferably 3 hours or less, from the viewpoint of production efficiency. On the other hand, in order to obtain a desired stress profile, the total treatment time is preferably 0.5 hours or more, and more preferably 1 hour or more.

[0082] The chemically strengthened glass in this embodiment obtained as described above may have a shape other than a plate shape depending on the product or application to which it is applied. The chemically strengthened glass may have a border shape with a different thickness on the periphery. The form of the chemically strengthened glass is not limited to this, and for example, the two main surfaces may not be parallel to each other, and one or both of the two main surfaces may be entirely or partially curved. More specifically, the chemically strengthened glass may be, for example, a flat glass plate without warping, or a curved glass plate having a curved surface.

[0083] The obtained chemically strengthened glass may be immersed in an alkaline solution to remove organic matter adhering to the surface. Alternatively, the main surface of the chemically strengthened glass may be irradiated with plasma in the atmosphere to remove organic matter adhering to the surface. By removing the organic matter adhering to the surface, the adhesion to the film formed on the main surface is increased, and durability is improved, which is preferable.

[0084] A low refractive index film is formed on the main surface of the chemically strengthened glass. The method of forming the low refractive index film varies depending on the film to be formed.

[0085] In the case where the low refractive index film is an adhesive layer that enhances adhesion, the film can be formed by chemical vapor deposition (CVD) or physical vapor deposition (PVD). Physical vapor deposition methods include vacuum deposition, ion-assisted sputtering (IAD), sputtering, post-oxidation sputtering, ion-assisted sputtering, ion beam sputtering, and ion beam assisted deposition. Among these, ion-assisted sputtering, post-oxidation sputtering, and ion beam assisted deposition are preferred because they can increase the hardness of the adhesive layer relatively easily.

[0086] The pressure in the chamber during vacuum deposition is preferably 0.15 Pa or less, more preferably 0.1 Pa or less, and more preferably 0.08 Pa or less, from the viewpoint of increasing the hardness of the adhesive layer. Moreover, from the viewpoint of stably maintaining plasma discharge, the pressure is preferably 0.03 Pa or more.

[0087] The sample for vacuum deposition to be the adhesive layer is preferably silicon dioxide (SiO2). The sample is placed in a heating vessel and evaporated by heating under low vacuum, and a film is formed on the main surface of a glass plate placed opposite the heating vessel.

[0088] When the sputtering method is used, from the viewpoint of increasing the hardness of the film, the discharge power during film formation is preferably 5000 W or more, more preferably 7000 W or more. Moreover, from the viewpoint of preventing cracking of the target and abnormal discharge, the discharge power is preferably 20000 W or less.

[0089] During the deposition of the adhesion layer, it is preferable to expose it to high energy particles from a plasma source, an ion source, a radical source, or the like, i.e., plasma assist is preferably performed every time a film is deposited to a thickness of 100 nm or less, more preferably every time a film is deposited to a thickness of 1 nm or less, and even more preferably every time a film is deposited to a thickness of 0.5 nm or less. The high energy particle source is not particularly limited in type, but ion beams such as plasma beams, ion beams, linear ion beams, ECR (Electron Cyclotron Resonance) plasma sources, radical sources, and low impedance antenna plasma sources, radical sources, ECR plasma sources, and the like are preferred.

[0090] The above steps are preferably carried out, for example, in a sputtering apparatus capable of carrying out a post-oxidation sputtering method (for example, RAS1100B II, manufactured by Shincron). When forming a SiO2 film as an adhesive layer, it is preferable to use a Si target, argon gas and oxygen gas as the discharge gas in the film formation chamber, and argon and oxygen as the discharge gas in the reaction chamber. In this device, a drum holding a substrate is placed in a vacuum chamber divided into a film formation chamber and a reaction chamber, and the drum holding the substrate rotates at, for example, 100 rpm while passing alternately through the film formation chamber and the reaction chamber at high speed. This forms a very thin film of less than a few nm in the film formation chamber. After that, energy may be added to the film sent to the reaction chamber by an active gas reacted by a plasma source, or the unreacted parts may be reacted.

[0091] In order to increase the hardness of the adhesion layer, it is preferable to use such a post-oxidation process device, and further, it is preferable to impart energy to the SiO2 film using a plasma source in the reaction chamber after forming the SiO2 film through a sufficient oxidation reaction in the film formation chamber.

[0092] In the case where the low refractive index film is an anti-fouling layer having one or more properties selected from the group consisting of anti-fouling properties, water repellency, oil repellency, hydrophilicity, and lipophilicity, examples of the method include wet methods such as spin coating, dip coating, casting, slit coating, and spray coating, and dry methods represented by vacuum deposition. In order to form an antifouling layer having high adhesion and high abrasion resistance, it is preferable to form it by a vacuum deposition method. Examples of the vacuum deposition method include a resistance heating method, an electron beam heating method, a high-frequency induction heating method, a reactive deposition method, a molecular beam epitaxy method, a hot wall deposition method, an ion plating method, and a cluster ion beam method. The resistance heating method is preferable because it requires a simple device and is low cost. The antifouling layer may be formed directly on the main surface of the chemically strengthened glass, or may be formed via another layer such as an adhesion layer.

[0093] The pressure in the chamber during vacuum deposition is set to 5×10 -3 From the viewpoint of maintaining a constant deposition rate of the antifouling layer, the pressure in the chamber during vacuum deposition is preferably 1×10 -4Pa or more is preferred.

[0094] The deposition output was set to 200 kA / m in terms of current density to prevent water from adsorbing onto the antifouling layer and ensure stable film formation. 2 More than 300kA / m is preferable. 2 More preferably, 350 kA / m 2 More preferably, the deposition output is 1000 kA / m or more from the viewpoint of preventing evaporation of the steel wool and the crucible components impregnated with the raw material of the antifouling layer. 2 The following is preferred:

[0095] The deposition sample is preferably held in a form in which the fluoro-organic compound constituting the antifouling layer is impregnated in a pellet-shaped copper container. The impregnation process is preferably carried out under a nitrogen atmosphere. In this way, the layer in which the fluoro-organic compound is deposited as a monoatomic molecule is increased, improving the abrasion resistance of the antifouling layer.

[0096] When the low refractive index film is an anti-reflection layer, it can be formed by, for example, a chemical vapor deposition (CVD) method or a physical vapor deposition (PVD) method. Examples of the physical vapor deposition method include a vacuum deposition method and a sputtering method.

[0097] <Surface stress measurement method> The measurement target of the surface stress measurement method according to the present embodiment is chemically strengthened glass having a pair of main surfaces opposed to each other, the pair of main surfaces having two or less interference fringes observed in stress measurement using surface-propagated light having a wavelength of 365 nm.

[0098] With chemically strengthened glass alone, two or fewer interference fringes are observed in stress measurements using surface-propagated light with a wavelength of 365 nm. Because the stress depth is shallow, the interference fringes are unclear, making it difficult or impossible to measure the surface compressive stress. However, by forming a film having a lower refractive index than the chemically strengthened glass on at least one of the main surfaces of the chemically strengthened glass, the interference fringes become clearer and the surface compressive stress can be easily measured.

[0099] That is, the surface stress measuring method according to this embodiment includes the following steps (1) and (2). (1) A process of forming a film (low refractive index film) having a lower refractive index than chemically strengthened glass on at least one main surface of chemically strengthened glass having two or less interference fringes observed in stress measurement using surface-propagated light having a wavelength of 365 nm to obtain chemically strengthened glass with a film; and (2) A process of measuring the surface compressive stress of the chemically strengthened glass by performing stress measurement using surface-propagated light on the obtained chemically strengthened glass with a film.

[0100] By forming a low refractive index film on the main surface of chemically strengthened glass, interference fringes can be clearly observed in stress measurement using surface-propagated light. The shorter the wavelength of the surface propagating light, the clearer and more numerous the observed interference fringes will be. The wavelength for stress measurement is not limited to 365 nm, and may be other wavelengths such as 596 nm or 790 nm. From the viewpoint of easily observing clear interference fringes, the wavelength of the surface propagating light is preferably 650 nm or less, more preferably 550 nm or less. In addition, when using FSM-6000LEUV manufactured by Orihara Seisakusho as a glass surface stress meter manufactured by Orihara Seisakusho, the lower limit of the wavelength is 365 nm, but if measurement is possible in the wavelength range below that, surface propagating light of less than 365 nm may be used. In addition, measurement may be performed using multiple wavelengths. EXAMPLES

[0101] The present invention will be described below with reference to examples, but the present invention is not limited thereto. Examples 1 and 6 to 19 are Reference Examples, Example 2 is a Comparative Example, and Examples 3 to 5 are Working Examples.

[0102] (Measurement method) The surface compressive stress and surface stress depth of the chemically strengthened glass were measured using a glass surface stress meter (Orihara Seisakusho, FSM-6000LEUV). The wavelength of the light source for the surface propagation light was 365 nm. The stress depth in the deep layers of the chemically strengthened glass and the tensile stress in the center of the glass were measured using a scattered light photoelastic stress meter (Orihara Seisakusho, SLP2000). The refractive index of the chemically strengthened glass was measured using a Kalnew precision refractometer KPR-2000 manufactured by Shimadzu Corporation. The refractive index of the low refractive index film was calculated based on previous knowledge.

[0103] (Example 1) Glass raw materials were mixed to obtain the composition shown in Table 1 in terms of oxide-based mole percentage, and then heated and melted. After homogenization, the glass was slowly cooled. The obtained glass was formed into a glass plate of 50 mm x 50 mm and a thickness t of 0.70 mm. Note that blanks in Table 1 indicate that no impurities were included except for unavoidable impurities contained in the raw materials, i.e., that the impurities were not intentionally included.

[0104] The obtained glass plate was immersed in molten NaNO3 at 380°C for 150 minutes to carry out the first stage of chemical strengthening treatment, and then immersed in molten KNO3 at 450°C for 60 minutes to carry out the second stage of chemical strengthening treatment, thereby obtaining chemically strengthened glass.

[0105] The obtained chemically strengthened glass was subjected to measurements of surface compressive stress, surface stress depth, deep layer stress depth, and tensile stress. The images obtained by the surface stress meter measurements are shown in Figure 1. The upper part of Figure 1 is an image measured with P-polarized light, in which six clear interference fringes are observed. The lower part of Figure 1 is an image measured with S-polarized light, in which five clear interference fringes are observed. This chemically strengthened glass had a surface compressive stress of 990 MPa, a surface stress depth of 7.5 μm, a deep layer stress depth of 127 μm, and a tensile stress of 84 MPa.

[0106] [Table 1]

[0107] (Example 2) A glass plate was obtained in the same manner as in Example 1, except that the glass thickness t was 0.75 mm. The obtained glass plate was immersed in molten NaNO3 salt at 380°C for 140 minutes to carry out the first stage of chemical strengthening treatment, and then immersed in molten KNO3 salt at 390°C for 50 minutes to carry out the second stage of chemical strengthening treatment, thereby obtaining chemically strengthened glass. The obtained chemically strengthened glass was subjected to measurements of surface compressive stress, surface stress depth, deep layer stress depth, and tensile stress.

[0108] Figure 2 shows the images obtained by measurement with the surface stress meter. The upper part of Figure 2 is an image measured with P-polarized light, in which two unclear interference fringes were observed. The lower part of Figure 2 is an image measured with S-polarized light, in which two unclear interference fringes were observed. In either case, the surface compressive stress and surface stress depth could not be determined by automatic measurement using the surface stress meter. Therefore, the position of the interference fringes was determined visually in Figure 2, and the surface compressive stress and surface stress depth were determined. This chemically strengthened glass had a surface compressive stress of 1220 MPa, a surface stress depth of 2.9 μm, a deep layer stress depth of 106 μm, and a tensile stress of 65 MPa.

[0109] (Example 3) Chemically strengthened glass was obtained in the same manner as in Example 2. The chemically strengthened glass was cleaned by immersing it in pure water and an alkaline detergent. Thereafter, the principal surface of the chemically strengthened glass on which the film was to be formed was irradiated with plasma to perform plasma cleaning. Next, a fluorine-based organic compound (UD-509, manufactured by Daikin) was used as a sample, and a low refractive index film A was formed on the main surface of the chemically strengthened glass by vacuum deposition using resistance heating, to obtain a chemically strengthened glass with a film. In this case, the sample was used in a state in which the sample liquid was impregnated into steel wool in a pellet-shaped copper container in a nitrogen atmosphere and the steel wool was supported by evacuation. The pressure in the vacuum chamber during the formation of the low refractive index film A was 3.0×10 -3 Pa, and the deposition output was 318.5 kA / m 2 The vapor deposition was performed for 300 seconds. The thickness of the low refractive index film A thus formed was 15 nm. The refractive index of the chemically strengthened glass was 1.54 at a wavelength of 365 nm and 1.52 at a wavelength of 589 nm, while the refractive index of the low refractive index film A was 1.40 to 1.42 at a wavelength of 589 nm. In other words, the difference between the refractive index of the low refractive index film A and the refractive index of the chemically strengthened glass was 0.10 to 0.12.

[0110] The images obtained by measurement with the surface stress meter are shown in Figure 3. The upper part of Figure 3 is an image measured with P-polarized light, and the lower part is an image measured with S-polarized light. In both cases, interference fringes were clearly observed compared to Example 2, where low refractive index film A was not formed, and automatic measurement with the surface stress meter was possible. The chemically strengthened glass had a surface compressive stress of 1220 MPa, a surface stress depth of 2.9 μm, a deep layer stress depth of 106 μm, and a tensile stress of 65 MPa.

[0111] (Example 4) Chemically strengthened glass was obtained in the same manner as in Example 2. The chemically strengthened glass was cleaned by immersing it in pure water and an alkaline detergent. Thereafter, the principal surface of the chemically strengthened glass on which the film was to be formed was irradiated with plasma to perform plasma cleaning. Next, a low refractive index film B was formed on the main surface of the chemically strengthened glass by sputtering. The sputtering device used was a RAS1100B II manufactured by Synchron. The low refractive index film B was a SiO2 film, and the sputtering target was polycrystalline Si (manufactured by Chemistone, purity 5N). The pressure in the film formation chamber was 5×10 -5 After confirming that the pressure was below 1 Pa, argon was introduced at 80 sccm as the discharge gas into the deposition chamber, and a power of 7500 W was applied to the sputtering target. Next, oxygen was introduced at 110 sccm into the reaction chamber, and the power of the RF plasma source was set to 3000 W to perform discharge. Under the above conditions, a low refractive index film B was deposited to a thickness of 5 nm. Subsequently, in the same manner as in Example 3, a low refractive index film A was formed on the low refractive index film B to obtain a film-coated chemically strengthened glass. The thickness of the low refractive index film A was 15 nm. The refractive index of the chemically strengthened glass was 1.54 at a wavelength of 365 nm and 1.52 at a wavelength of 589 nm, while the refractive index of the low refractive index film A was 1.40 to 1.42 at a wavelength of 589 nm. In other words, the difference between the refractive index of the low refractive index film A and the refractive index of the chemically strengthened glass was 0.10 to 0.12. In addition, the refractive index of the low refractive index film B was 1.49 at a wavelength of 365 nm and 1.47 at a wavelength of 589 nm. In other words, the difference between the refractive index of the low refractive index film B and the refractive index of the chemically strengthened glass was 0.05.

[0112] The images obtained by the measurement with the surface stress meter are shown in Figure 4. The upper part of Figure 4 is an image measured with P-polarized light, and the lower part is an image measured with S-polarized light. In both cases, interference fringes were clearly observed compared to Example 2, where neither low refractive index film A nor low refractive index film B was formed, and automatic measurement with the surface stress meter was possible. The chemically strengthened glass had a surface compressive stress of 1240 MPa, a surface stress depth of 2.9 μm, a deep layer stress depth of 106 μm, and a tensile stress of 65 MPa.

[0113] (Example 5) A chemically strengthened glass with a film was obtained in the same manner as in Example 4, except that the thickness of the low refractive index film B was 10 nm. The film formation conditions for the low refractive index film B were as follows. Argon was introduced as the discharge gas into the deposition chamber at 80 sccm, and a power of 7500 W was applied to the sputtering target. Then, oxygen was introduced into the reaction chamber at 110 sccm, and the power of the RF plasma source was set to 3000 W to perform discharge. Under the above conditions, a low refractive index film was deposited to a thickness of 10 nm. The refractive index of the chemically strengthened glass was 1.54 at a wavelength of 365 nm and 1.52 at a wavelength of 589 nm, while the refractive index of the low refractive index film A was 1.40 to 1.42 at a wavelength of 589 nm. In other words, the difference between the refractive index of the low refractive index film A and the refractive index of the chemically strengthened glass was 0.10 to 0.12. In addition, the refractive index of the low refractive index film B was 1.49 at a wavelength of 365 nm and 1.47 at a wavelength of 589 nm. In other words, the difference between the refractive index of the low refractive index film B and the refractive index of the chemically strengthened glass was 0.05.

[0114] The images obtained by the measurement with the surface stress meter are shown in Figure 5. The upper part of Figure 5 is an image measured with P-polarized light, and the lower part is an image measured with S-polarized light. In both cases, interference fringes were clearly observed compared to Example 2, where neither low refractive index film A nor low refractive index film B was formed, and automatic measurement with the surface stress meter was possible. The chemically strengthened glass had a surface compressive stress of 1240 MPa, a surface stress depth of 2.9 μm, a deep layer stress depth of 106 μm, and a tensile stress of 65 MPa.

[0115] (Example 6 to Example 19) Chemically strengthened glasses of Examples 6 to 19 were obtained in the same manner as in Example 1, except that glass raw materials were prepared so as to have the compositions shown in Table 1 in terms of mole percentages based on oxides.

[0116] From the above results, it was found that when the surface stress depth is made shallow by ion exchange between potassium ions and sodium ions, the interference fringes become unclear or the number of fringes decreases in the surface stress measurement, and the surface compressive stress and surface stress depth cannot be measured automatically using a surface stress meter. In response to this, by forming a low refractive index film on the main surface of the chemically strengthened glass, the interference fringes become clearer, making it possible to measure the surface compressive stress and surface stress depth automatically.

Claims

1. A chemically strengthened glass having a pair of main surfaces facing each other, and a film formed on at least one of the main surfaces of the chemically strengthened glass, The chemically strengthened glass has two or less interference fringes observed in stress measurement using surface-propagated light having a wavelength of 365 nm, A chemically strengthened glass with a film, wherein the refractive index of the film is lower than the refractive index of the chemically strengthened glass.

2. The chemically strengthened glass with a film according to claim 1, wherein the difference between the refractive index of the film and the refractive index of the chemically strengthened glass is 0.02 to 0.

30.

3. The chemically strengthened glass with a film according to claim 1 or 2, wherein a stress depth of a deep layer of the chemically strengthened glass is 0.1 × t or more, when a thickness of the chemically strengthened glass is t.

4. The base composition of the chemically strengthened glass is expressed in mole percentage based on oxides, and Li 2 The chemically strengthened glass with a film according to any one of claims 1 to 3, containing 5 mol% or more of O.

5. The chemically strengthened glass with a film according to any one of claims 1 to 4, wherein the film has a thickness of 2 to 50 nm.

6. The chemically strengthened glass with a film according to any one of claims 1 to 5, wherein the film contains a fluorine-based organic compound.

7. A method for measuring surface stress of chemically strengthened glass having a pair of main surfaces facing each other, The chemically strengthened glass has two or less interference fringes observed in stress measurement using surface-propagated light having a wavelength of 365 nm, Forming a film having a lower refractive index than the chemically strengthened glass on at least one main surface of the chemically strengthened glass to obtain a film-coated chemically strengthened glass; and A surface stress measuring method for chemically strengthened glass, comprising: performing stress measurement on the film-coated chemically strengthened glass using surface-propagating light, and measuring a surface compressive stress of the chemically strengthened glass.

8. The surface stress measuring method for chemically strengthened glass according to claim 7, wherein the surface propagating light for the film-coated chemically strengthened glass has a wavelength of 650 nm or less.

Citation Information

Patent Citations

  • Method and device for automatically inspecting vessel

    JP1984037451A

  • Surface refractive index measurement method and surface stress measurement method using the same

    JP6713651B2

  • Strengthened glass with deep depth of compression

    US9487434B2

  • Cover glass, and in-cell liquid-crystal display device

    WO2019159983A1

  • Contamination prevention layer-attched glass substrate and method for manufacturing contamination prevention layer-attached glass substrate

    WO2020171091A1